CRYSTAL STRUCTURE AND COMPRESSION OF AN IRON-BEARING PHASE A TO 33 GPA - Holl C.M.; Smyth J.R.; Manghnani M.H.; Amulele G.M.; Sekar M.; Frost D.J.; Prakapenka V.B.; Shen G. (My University, 2006)
Fe-bearing dense hydrous magnesium silicate Phase A, Mg6.85Fe0.14Si2.00O8(OH)6 has been studied by single-crystal X-ray diffraction at ambient conditions and by high-pressure powder diffraction using synchrotron radiation to 33 GPa. Unit cell parameters at room temperature and pressure from single crystal diffraction are a=7.8678 (4) Å, c=9.5771 (5) Å, and V=513.43 (4) Å3. Fitting of the P–V data to a third-order Birch-Murnaghan isothermal equation of state yields V 0=512.3 (3) Å3, K T,0=102.9 (28) GPa and K′=6.4 (3). Compression is strongly anisotropic with the a-axes, which lie in the plane of the distorted close-packed layers, approximately 26% more compressible than the c-axis, which is normal to the plane. Structure refinement from single-crystal X-ray intensity data reveals expansion of the structure with Fe substitution, mainly by expansion of M-site octahedra. The short Si2–O6 distance becomes nearly 1% shorter with ~2% Fe substitution for Mg, possibly providing additional rigidity in the c-direction over the Mg end member. K T obtained for the Fe-bearing sample is ~5.5% greater than reported previously for Fe-free Phase A, despite the larger unit cell volume. This study represents a direct comparison of structure and K T–ρ relations between two compositions of a F-free dense hydrous magnesium silicate (DHMS) phase, and may help to characterize the effect of Fe substitution on the properties of other DHMS phases from studies of the Fe-free end-members.
Keywords: PHASE A; HIGH PRESSURE; HYDROUS SILICATES; DHMS; CRYSTAL STRUCTURE; BULK MODULUS